Chylothorax and Recurrent Laryngeal Nerve Injury Associated with Robotic Video-Assisted Mediastinal Lymph Node Dissection. Issue 3 (May 2015) - Sarkaria, Inderpal S.; Finley, David J.; Bains, Manjit S.; Adusumilli, Prasad S.; Rizk, Nabil P.; Huang, James; Downey, Robert J.; Rusch, Valerie W.; Jones, David R.
Objective: Although the technical aspects of robotic video-assisted thoracic surgery (RVATS) for lung resections may be advantageous, compared with standard thoracoscopy, complications of chylothorax and recurrent laryngeal nerve injury (RLNI) associated with mediastinal lymph node dissection (MLND) may be significant. Methods: Consecutive patients who underwent RVATS anatomic lung resection for suspected or confirmed cancer and experienced RLNI or chylothorax were identified and reviewed from a prospectively maintained database. Complications were graded according to the Common Terminology Criteria for Adverse Events version 3.0. Results: From July 28, 2010, to December 20, 2013, 251 patients underwent RVATS segmentectomy, lobectomy, or bilobectomy with MLND. Eleven patients (4.4%) experienced MLND-related complications and composed the study group; 81.8% were right-sided resections, and the median lymph node counts in right station IV and station VII were 9 (range, 1–23) and 5.5 (range, 1–10); 72.7% of the cases were performed for early-stage I and II lung cancers. Chylothorax [6/251 (2.4%)] and RLNI [6/251 (2.4%)] were significantly more common in the RVATS group than in the open thoracotomy and standard VATS groups. Complications requiring procedural intervention (Grade 3) are as follows: 4 cases of RLNI in patients undergoing percutaneous vocal cord medialization and 3 cases of chylothorax in patients undergoing image-guided thoracic duct embolization or maceration. No operative interventions were required. Conclusions: RVATS MLND may be associated with increased rates of chylothorax and RLNI. Attention must be paid to identifying potential technical pitfalls with RVATS lung resections, adjusting surgical techniques accordingly, and minimizing patient morbidity.